Strategi Hubungan Masyarakat dalam Pendidikan Islam - Rozi, M. Asep Fathur (Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2017)
ABSTRACT: Public Relations is the management function which evaluates public attitudes, indentifies the policies and procedures of an inividual or organization with the public interest and axecutes a program of action to earn public understanding and acceptance. The principle of Public relations are Qaulan MaÃ¢â¬â¢ruf, Qawlan Syahid,Qaulan Baligha, Qaulan Karimah, Qaulan Maysurah, dan Qaulan Layyinah. The relationship between school and internal public can be done by extracurricular, field trip, camping, field practice, internal meeting with teacher and community service. Strategy school in establish external public could be done in a form of report to students parents, school magazine, school exhibition, open house, school visitation, radio and television, letters and telephone. A synergy between educational institutions with the community (parents) can be created by taking the community as a partner. This level higher than only become the community as customer. In this case the community or parents involved in the policy making and planning in education. Thus people to determine the development of educational institutions that eventually impact on child development.